Developing a model of industry-based practicum learning - Bambang Sudarsono; Thomas Sukardi (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2017)
The study was to: (1) produce a practicum learning model that might be applied by the lecturers of Automotive Engineering Education Program as the center of Light Vehicle Engineering (LVE) Study Program prospective teachers in the vocational high schools (VHS); (2) identify the automotive industry-oriented competence aspects in practicum learning needed by the LVE Study Program prospective teachers in the VHS; (3) identify the degree of implementatibility of the practicum learning model that had been developed for the LVE Study program prospective teachers in the VHS; and (4) identify the effectiveness degree of the practicum learning model that had been developed for the LVE Study Program prospective teachers in the VHS. The model development in the study referred to the research and development model proposed by Richey and Klein. The research subjects were the students of Automotive Engineering Education Study Program Muhammadiyah University Purworejo. Then, the research objects were Toyota Magelang Company, the Daihatsu Armada Company and the Ultratune Company Gadjah Mada University. The results of the study show that: (1) the competency aspects developed in the P2BI Model for the students who refer the LVE Study Program prospective teachers include the affective aspect, the cognitive aspect and the psychomotor aspect; (2) the improvement of the affective, the cognitive and the psychomotor aspect has met the